Satisfaction With Life, Well-Being, and Meaning in Life as Protective Factors of Eating Disorder Symptoms and Body Dissatisfaction in Adolescents - Gongora, Vanesa Carina (2014)
This study aimed to investigate the relationship among three potential protective factors: satisfaction with life, three routes to well-being and meaning in life, and eating disorder symptoms and body dissatisfaction in male and female adolescents. The sample was composed of 247 adolescent students aged 13 to 18 years. The findings of this study support the protective roles of satisfaction with life and engagement as routes to well-being in male adolescents and particularly in female adolescents. Positive interventions to promote satisfaction with life and engagement in activities in school are highly recommended.